Advances in Artificial Economics The Economy as a Complex Dynamic System - Bruun, Charlotte (Lecture Notes in Economics and Mathematical Systems, 2006)
Perceiving the economy as a complex dynamic system, generates a need for new tools for its study. As a constructive simulation method, Agent-Based Computational Economics (ACE) has in recent years proven its strength and extensive applicability. Fields of study are widely spread within economics, with a cluster around financial markets. This book is based on communications given at AE'2006 (Aalborg, Denmark) - the second symposium on Artificial Economics, and covers both wellknown questions of economics, like the existence of market efficiency, as well as new questions raised by the new tools, for example questions related to networks of social interaction.